1992
DOI: 10.1111/j.1526-4610.1992.hed3205233.x
|View full text |Cite
|
Sign up to set email alerts
|

Olfaction in Migraineurs

Abstract: Many investigators have described olfactory dysfunction among migraineurs. Olfactory stimuli can precipitate migraine, and olfactory hallucinations can occur as auras of migraines or as part of the symptom complex. Despite many reports linking olfactory phenomena and migraine, no evaluations of the olfactory abilities of migraineurs have been documented. To begin such assessments, sixty-seven consecutive migraine patients were given Pyridine odor threshold tests. Twelve of them (18%) scored as hyposmic or anos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 6 publications
4
33
2
Order By: Relevance
“…Stress was the commonest triggering factor (72.1%) which is consistent with other studies [17] [17], [26], [28], [33], [34], [35], [36] , [37], [38] .…”
Section: Discussionsupporting
confidence: 81%
“…Stress was the commonest triggering factor (72.1%) which is consistent with other studies [17] [17], [26], [28], [33], [34], [35], [36] , [37], [38] .…”
Section: Discussionsupporting
confidence: 81%
“…There are contradictory results that show the presence of sensorial hyperacuity to odours in migraineurs [11], but also that migraineurs can be more anosmic or hyposmic than normal subjects [12]. The less common prevalence of osmophobia in migraine, compared to phono-or photophobia, can suggest that only severe painful attacks can activate the olfactory system, while the activation threshold is lower for the visual and auditory systems.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of persons with migraine to detect and discriminate odors, as determined by standardized olfactory testing, is less clear. In one study, a large number of migraine subjects had poor olfactory acuity [10], as measured by olfactory thresholds, and in another migraineurs had increased odor detection [11]. A more recent study of episodic migraine subject found that their olfactory acuity was normal [5].…”
Section: Introductionmentioning
confidence: 99%